2019
DOI: 10.1177/1753425919867746
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of icariin and phosphorylated icariin against LPS-induced intestinal goblet cell dysfunction

Abstract: In this study, we used LS174T cells as a model to investigate the protective effects of icariin and phosphorylated icariin on LPS-induced goblet cell dysfunction. Our results indicated that icariin and phosphorylated icariin increased the cell viability and decreased lactate dehydrogenase activity in LPS-treated LS174T cells. Icariin and phosphorylated icariin attenuated LPS-induced changes in mucin 2 synthesis and secretion. Besides, Icariin and phosphorylated icariin reduced the levels of ROS, MDA, and H2O2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 50 publications
(61 reference statements)
2
13
0
Order By: Relevance
“…Intriguingly, treatment of ICA significantly repressed the expression of IL-1β, IL-6, and TNF-α as well as boosted the production of IL-10. The findings of current research are in-line with the previous reports [ 27 , 38 ]. Hence, we concluded that ICA might express its protective effect by attenuation of the production of IL-1β, IL-6, and TNF-α as well as boosting the production of IL-10 in LPS-induced endometritis.…”
Section: Discussionsupporting
confidence: 93%
“…Intriguingly, treatment of ICA significantly repressed the expression of IL-1β, IL-6, and TNF-α as well as boosted the production of IL-10. The findings of current research are in-line with the previous reports [ 27 , 38 ]. Hence, we concluded that ICA might express its protective effect by attenuation of the production of IL-1β, IL-6, and TNF-α as well as boosting the production of IL-10 in LPS-induced endometritis.…”
Section: Discussionsupporting
confidence: 93%
“…Similar effects were observed in HUVECs [11,23]. Reducing oxidative stress alleviates inflammatory cytokine production, thereby reducing the availability of various signaling factors, including TNF-α and IL1β [24]. In this study, the administration of 4HR decreased the expression levels of TNF-α and IL1β, which were elevated in response to hydrogen peroxide (Figure 2).…”
Section: Discussionsupporting
confidence: 79%
“…It has been reported that MOS supplementation could increase the number of goblet cells in European sea bass ( 24 ). Another study has confirmed that abnormal goblet cell proliferation can produce excess mucus, leading to the occurrence of inflammation in LS174T cells ( 44 ). Our results also showed that the expression of the inflammatory cytokines in the high dose MOS group (1000 mg/kg) was significantly higher than that of the more optimal MOS groups (400-600 mg/kg), indicating that excessive MOS is not conducive to the recovery of intestinal homeostasis after the challenge.…”
Section: Discussionmentioning
confidence: 87%